Strategic proposal towards 2030: Student knowledge, curricular flexibility and teaching innovation - Rivarola Padrós, Pablo (Rastros Rostros, 2026)
This article presents a strategic proposal towards 2030 for the Universidad Cooperativa de Colombia, aimed at strengthening its cooperative and multi-campus identity through the integration of student knowledge, curricular flexibility, and teaching innovation. Drawing on global trends in higher education—such as learning analytics, competency-based education, responsible use of artificial intelligence, micro-credentials, and student wellbeing—the paper outlines a roadmap that combines continuous student profiling, matrix-based curricular redesign, and academic staff development as key drivers of institutional transformation. The proposal highlights the role of faculty as learning experience designers, ethical mediators, and contemporary polymaths, while advocating for flexible, relevant, and equitable educational pathways. It concludes that cooperative identity can function as an adaptive advantage in addressing employability, territorial engagement, and social legitimacy challenges in higher education by 2030.
Keywords: Higher education; Educational innovation; Curriculum; Competency-based education; Educational policy